Traditional Medicinal Plants—A Possible Source of Antibacterial Activity on Respiratory Diseases Induced by Chlamydia pneumoniae, Haemophilus influenzae, Klebsiella pneumoniae and Moraxella catarrhalis - Ligia Elena Duțu; Maria Lidia Popescu; Carmen Nicoleta Purdel; Elena Iuliana Ilie; Emanuela-Alice Luță; Liliana Costea; Cerasela Elena Gîrd (Diversity, 2022)
Background. Nowadays, phytotherapy offers viable solutions in managing respiratory infections, disorders known for considerable incidence in both children and adults. In a context in which more and more people are turning to phytotherapy, finding new remedies is a topical goal of researchers in health and related fields. This paper aims to identify those traditional medicinal plants that show potentially antibacterial effects against four Gram-negative germs (Chlamydia pneumoniae, Haemophilus influenzae, Klebsiella pneumoniae, and Moraxella catarrhalis), which are considered to have high involvement in respiratory infections. Furthermore, a comparison with Romanian folk medicines was performed. Methods. An extensive review of books and databases was undertaken to identify vegetal species of interest in the context of the topic. Results. Some traditional Romanian species (such as Mentha × piperita, Thymus vulgaris, Pinus sylvestris, Allium sativum, Allium cepa, Ocimum basilicum, and Lavandulaangustifolia) were identified and compared with the plants and preparations confirmed as having antibacterial effects against specific germs. Conclusions. The antibacterial effects of some traditionally used Romanian medicinal plants are poorly investigated, and deserve further attention.